2017
DOI: 10.1534/genetics.117.300198
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Gene Annotation into Genomic Prediction of Complex Phenotypes

Abstract: Today, genomic prediction (GP) is an established technology in plant and animal breeding programs. Current standard methods are purely based on statistical considerations but do not make use of the abundant biological knowledge, which is easily available from public databases. Major questions that have to be answered before biological prior information can be used routinely in GP approaches are which types of information can be used, and at which points they can be incorporated into prediction methods. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 47 publications
6
43
0
Order By: Relevance
“…These results are similar to those of a previous study (Morgante et al, 2019), but higher than the results in (Li et al, 2019). This may be due to the quality control of the SNPs, the number of lines, and the line means for phenotypes in the present study, which are the same as those used in (Morgante et al, 2019) and different from those in (Gao et al, 2017). The high heritability of the analyzed traits showed that most loci that affect the traits have additive gene actions or contributions from non-additive gene actions at many loci.…”
Section: Total Genomic Heritability and Prediction Accuracysupporting
confidence: 88%
See 1 more Smart Citation
“…These results are similar to those of a previous study (Morgante et al, 2019), but higher than the results in (Li et al, 2019). This may be due to the quality control of the SNPs, the number of lines, and the line means for phenotypes in the present study, which are the same as those used in (Morgante et al, 2019) and different from those in (Gao et al, 2017). The high heritability of the analyzed traits showed that most loci that affect the traits have additive gene actions or contributions from non-additive gene actions at many loci.…”
Section: Total Genomic Heritability and Prediction Accuracysupporting
confidence: 88%
“…Therefore, pre-selected potential causal markers or QTLs from WGS are necessary for improving the accuracy of genomic prediction (Raymond et al, 2018). Thus, many preselection variant strategies were used to improve the power of genomic prediction based on the following methods: genomewide association study (GWAS) (Zhang et al, 2014;Veerkamp et al, 2016;Song et al, 2019;Ye et al, 2019), Bayesian procedures (Kemper et al, 2015), genome-wide signatures of selection (Ye et al, 2020), Animal QTLdb (Song et al, 2019), gene annotation (Heidaritabar et al, 2016;Gao et al, 2017), and gene ontology categories (Edwards et al, 2016;Abdollahiarpanahi et al, 2017). These methods mainly depend on the direct link between phenotype and DNA variants or some prior genome annotation information.…”
Section: Introductionmentioning
confidence: 99%
“…This has been accomplished by allowing pairwise relationships with all markers across entire subgenomes (Santantonio et al 2019b) or on syntenic chromosome arms (Santantonio et al 2019a), with mixed success. The construction of smaller haplotypes in a manner similar to Gao et al (2017) may also improve functional pairing of homeologous alleles. Higher depth sequencing and advances in marker imputation may also aid in detection of homeologous epistasis.…”
Section: Further Considerationsmentioning
confidence: 99%
“…This has been accomplished by allowing pairwise relationships with all markers across entire subgenomes (Santantonio et al ., 2018b) or on syntenic chromosome arms (Santantonio et al ., 2018a), with mixed success. The construction of smaller haplotypes in a manner similar to Gao et al ., (2017) may also improve functional pairing of homeologous alleles. Higher depth sequencing and advances in marker imputation may also aid in detection of homeologous epistasis.…”
Section: Further Considerationsmentioning
confidence: 99%